PENGARUH BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA, KOMITMEN ORGANISASIONAL DAN INTENTION TO LEAVE (Studi pada Karyawan PT.Bitung Mina Utama) - Steven Set Xaverius (University of Merdeka Malang, 2016)
The objective of this study is to analyze and explain the effect of Organizational Culture on Job Satisfaction, Organizational Commitment, and Intention to Leave.The research belongs to explanatory research. The samples are taken by using propotionate random sampling technique and the size of the samples to be determined 79 of 98 employes of PT. Bitung Mina Utama. The data collecting technique is questionnaire. The data is analyzed by using Path Analysis.The findings of this study show: (1) Organizational Culture has significant effect on Organizational Commitment; (2) Organizational Culture has significant effect on Job Satisfaction; (3) Organizational Culture has insignificant effect on Intention to Leave; (4) Job Satisfaction has significant effect on Organizational Commitment; (5) Job Satisfaction has insignificant effect on Intention to Leave; and (6) Organizational Commitment has significant effect on Intention to Leave.